Occupational Fatigue and Associated Factors among Saudi Nurses Working 8-Hour Shifts at Public Hospitals - Sharifah Abdulmuttalib Alsayed; Ebtsam Aly Abou Hashish; Farhan Alshammari (SAGE Publishing, 2022)
Introduction Shift work and demanding work schedules contribute to occupational fatigue, negatively affecting patient safety and nurses' well-being, consequently placing nurses and patients at risk for injury and adverse health outcomes. For preventing fatigue and minimizing its negative consequences, information about its characteristics and associated factors is required. Objectives This study aimed to assess occupational fatigue "acute fatigue, chronic fatigue, and inter-shift recovery" among Saudi nurses working 8-h shifts. Further, we explored factors associated with fatigue from nurses' perspectives. Methods We conducted a mixed-method study with a convenience sample of Saudi nurses ( N  = 282) working in four public hospitals in Saudi Arabia. Data were collected using the nurses' profile form; the occupational fatigue exhaustion recovery (OFER) scale, for relevant quantitative data; and open-ended questions for qualitative data. We used descriptive and inferential statistics for analysing the quantitative data and content analysis of the qualitative data. Results The results showed that Saudi nurses rated themselves moderately fatigued with working 8-h shifts. The inter-shift recovery subscale showed a negative correlation with chronic fatigue and acute fatigue ( r  = −0.518, r  = −0.356, P  < 0.001). Sleeping problems, meals per day, and frequency of exercise showed significant relations with chronic fatigue among nurses ( p  < 0.05). In addition, three categories were derived from the qualitative content analysis. Saudi nurses reported work-related, psychosocial, and individual factors as major contributors to fatigue and recovery. Conclusion Occupational fatigue is a multidimensional issue, and nurses and nurse managers are challenged with reducing its prevalence and negative impact on nurses and patients. Our quantitative and qualitative findings suggest the need for a comprehensive approach to fatigue management and mitigation, including organizational support, creative workforce planning, flexible work schedules, and psychosocial support. Fatigue reduction and prevention policies and educational programs are vital strategies to improve nurses' well-being and inter-shift recovery.